2019
DOI: 10.1080/21623945.2019.1636627
|View full text |Cite
|
Sign up to set email alerts
|

A MetAP2 inhibitor blocks adipogenesis, yet improves glucose uptake in cells

Abstract: Adipose tissue expansion involves angiogenesis to remodel its capillary network. The enzymemethionine aminopeptidase 2(MetAP2) promotes angiogenesis.MetAP2 inhibitors suppress angiogenesis and have potential anti-obesity effect. However, impairment in adipose tissue expansion is also linked with impaired glycemic control.This study investigated the effect of BL6, a MetAP2 inhibitor, on adipogenesis and glucose disposal.To test effect on angiogenesis, Human Umbilical Vein Endothelial Cells(HUVECs) were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…However, recent studies have shown that inhibition of MetAP2 is a strong candidate for treating obesity and diabetes ( Joharapurkar et al, 2014 ). Inhibition of MetAP2 induced clinically meaningful reductions in blood glucose and increased weight loss ( Siddik et al, 2019 ; Wentworth et al, 2020 ). The clinical agent ZGN-1061 is a MetAP2 inhibitor with promising results with improved glucose control and lowered weight in preclinical studies and a recently completed phase II clinical trial ( Burkey et al, 2018 ; Wentworth et al, 2020 ).…”
Section: Novel Drug Targetsmentioning
confidence: 99%
“…However, recent studies have shown that inhibition of MetAP2 is a strong candidate for treating obesity and diabetes ( Joharapurkar et al, 2014 ). Inhibition of MetAP2 induced clinically meaningful reductions in blood glucose and increased weight loss ( Siddik et al, 2019 ; Wentworth et al, 2020 ). The clinical agent ZGN-1061 is a MetAP2 inhibitor with promising results with improved glucose control and lowered weight in preclinical studies and a recently completed phase II clinical trial ( Burkey et al, 2018 ; Wentworth et al, 2020 ).…”
Section: Novel Drug Targetsmentioning
confidence: 99%
“…In one study, addition of fumagillin to an in vitro pre-adipocyte differentiation assay promoted adipogenesis, but had minimal effects in an in vivo adipogenesis assay 31 . In contrast in another study, addition of a fumagillin derivative to an in vitro pre-adipocyte differentiation study inhibited adipogenesis, yet fumagillin treatment of cells caused enhanced glucose uptake, suggesting metabolically healthier cells 32 . Alternatively, fumagillin has anti-angiogenic effects and a prevailing hypothesis is that changes in angiogenesis induced by fumagillin reduce adipose tissue mass.…”
Section: Discussionmentioning
confidence: 73%
“…In one study, addition of fumagillin to an in vitro preadipocyte differentiation assay promoted adipogenesis but had minimal effects in an in vivo adipogenesis assay (30). In contrast, another study showed that a fumagillin derivative inhibited adipogenesis in an in vitro preadipocyte differentiation study, but fumagillin treatment of cells enhanced glucose uptake, indicative of metabolically healthier cells (31). Alternatively, a prevailing hypothesis is that the antiangiogenic effects of fumagillin reduce adipose tissue mass, yet angiogenesis changes did not drive reduction of adipose tissue mass in mice (10).…”
Section: Discussionmentioning
confidence: 99%